Translation, Adaptation and Validation of Relational Betrayal Trauma Scale in English (Journal of Asian Development Studies, 2024)
The phenomenon of relational betrayal trauma, which involves severe violations of trust within close relationships (non-romantic), has become a noteworthy issue among young adults in several cultural settings. The study investigated the psychometric properties (reliability and validity) of the relational betrayal trauma scale (English version) in young adults. The data was collected from university students (M= 3.300, SD= 0.622) currently enrolled in graduation and post-graduation degrees from different universities in Faisalabad. The sample size comprised N=600 (males=300, females=300) young adults for a cross-sectional study. The data was collected using the purposive sampling method. The scale administration includes the Relational Betrayal Trauma Scale (Akram & Iftikhar, 2022), Brief Betrayal Trauma Survey (Goldberg & Freyd, 2016), and Multidimensional Scale of Perceived Social Support (Zimet, 2016). Statistical Package for Social Sciences 26 and AMOS 27 were used for data analysis. The results demonstrated good psychometric properties of relational betrayal trauma. The result demonstrated that relational betrayal trauma was reliable (α=.845). The convergent validity of the relational betrayal trauma scale with the brief betrayal trauma survey demonstrated a negative correlation (r= -.144, p < 0.05). The discriminate validity of the relational betrayal trauma scale with a multidimensional scale of perceived social support demonstrated a negative correlation (r= -.248, p < 0.01). The present study translated and adapted an indigenous scale in English to be used at the international level for English-speaking people. It is helpful for psychologists to understand trauma due to relational betrayal.